Experimental Investigation of the Relationship between the P-Wave Velocity and the Mechanical Properties of Damaged Sandstone - Qi-Le Ding; Shuai-Bing Song (Advances in Materials Science and Engineering)
To obtain an improved and more accurate understanding of the relationship between the P-wave velocity and the mechanical properties of damaged sandstone, uniaxial compression tests were performed on sandstone subjected to different high-temperature treatments or freeze-thaw (F-T) cycles. After high-temperature treatment, the tests showed a generally positive relationship between the P-wave velocity and mechanical characteristics, although there were many exceptions. The mechanical properties showed significant differences for a given P-wave velocity. Based on the mechanical tests after the F-T cycles, the mechanical properties and P-wave velocities exhibited different trends. The UCS and Young’s modulus values slightly decreased after 30, 40, and 50 cycles, whereas both an increase and a decrease occurred in the P-wave velocity. The UCS, Young’s modulus, and P-wave velocity represent different macrobehaviors of rock properties. A statistical relationship exists between the P-wave velocity and mechanical properties, such as the UCS and Young’s modulus, but no mechanical relationship exists. Further attention should be given to using the P-wave velocity to estimate and predict the mechanical properties of rock.